Reforma do ensino médio: negação do direito à educação a estudantes de escolas públicas em Soure – Ilha de Marajó - PA - BRITO, Raimara Suane Pantoja de (2024)
Considering that the reform of high school is a subject of significant educational and social impact that affects the future of students in Brazilian public schools, this research explores the High School Reform: denial of the right to education for students in public schools in Soure – Marajó Island - PA, in order to analyze the provisions included in the high school reform that express the denial of the right to education for students in public schools in Soure – Marajó Island – PA. Therefore, it is necessary to discuss the context of the high school reform and the changes in the curriculum organization of the last stage of basic education; highlight some problems that interfere with the educational process of students in public high schools, and discuss the quality of high school education offered in Brazilian public schools in the city of Soure, in Marajó, based on data related to school progression, approval, failure, dropout, and age-grade distortion. A descriptive research is then carried out that”[...] is restricted to verifying what already exists. The events are narrated [...]” (FURTADO; DUARTE, 2014, p. 26) and exploratory that “[...] their purpose is to provid greater familitarity with the problem, with a view to making it more explicito r building hypotheses” (GIL, 2010, p. 27) of a qualitative and quantitative nature and approach, is it analyzes and interprets human behavior both subjectively and also uses numerical data (MARCONI and LAKATOS, 2011). It is a documentary and bibliographical research. Which had a theoretical basis based on: BRASIL (1996,2017), Araújo (2018, 2019), Ciavatta (2018), Ferretti (2018), Krawczyk and Ferretti (2017), among others. The findings indicate that the factors affecting the educational context of high school in the city of Soure, according to our research results, include high levels of social vulnerability, high rates of failure, dropout, and age-grade distortion, lack of schools in rural areas, appropriate school transportation for land and river areas, and infrastructure. Therefore, we assert that such reform will not solve the educational problems in the context of high school but will further propagate the educational and social inequalities already present in this stage of basic education.